Silicon modulates nitro‐oxidative homeostasis along with the antioxidant metabolism to promote drought stress tolerance in lentil plants. Issue 2 (6th May 2021) - Biju, Sajitha; Fuentes, Sigfredo; Gupta, Dorin
Abstract: Lentil is the fifth most important grain legume growing in arid/semi‐arid regions of the world. Drought is one of the major constraints leading up to 50% of production losses just in lentil. Application of silicon (Si) has been shown to be a promising solution to improve drought tolerance; however, the biochemical mechanisms and interactions involved are not fully understood, especially in legumes. This study was designed to evaluate the effects of Si on drought stress tolerance of lentil genotypes. Seven lentil genotypes with different drought tolerance levels (tolerant, moderately tolerant and sensitive) were subjected to moderate and severe drought stress at the onset of the reproductive stage. Results showed that different drought stress treatments significantly decreased the above ground biomass, water status and the concentration of chlorophyll pigments, whereas Si supplementation of drought stressed lentil genotypes significantly improved the same traits, irrespective of their drought tolerant levels. On the other hand, Si effect on osmoregulation leads to a decline in the membrane damage and osmolytes (proline and glycine betaine) concentration in drought‐stressed lentil. Application of Si to drought‐stressed lentil plants significantly maintained the nitro‐oxidative homeostasis by balancing the concentrations of reactive oxygen/nitrogen species, superoxide anion, hydrogen peroxide and nitrous oxide, thereby reducing the oxidative damage caused due to drought stress. Furthermore, Si supplementation also stimulated the efficiency of the glutathione (GSH)‐ascorbate (ASC) cycle by increasing the concentrations of GSH and ASC as well as the activities of antioxidant enzymes like ascorbate peroxidase, guaiacol peroxidase, catalase, superoxide dismutase, glutathione reductase, dehydro‐ascorbate reductase and nitrate reductase for better protection of cell membranes from reactive oxygen species. Although Si showed the same regulatory mechanisms in all the studied genotypes to protect lentil plants from moderate and severe drought stress, the defensive role of Si against drought stress was more conspicuous in drought sensitive genotypes than in the tolerant ones. Thus, this study suggests the protective role of Si on drought‐stressed lentil genotypes through the modulation of nitro‐oxidative homeostasis and antioxidant defence responses.